Developing a Successful Master of Health Administration Student Mentor-Mentee Program. Issue 1 (January 2016) - Shaikh, Aliya; AlTurabi, Layla; West, Daniel J.
Abstract : A student mentoring program can impact the overall experience in an academic program and establish a strong connection between students. It creates a platform for students to ask specific questions, learn more about the curriculum and professional opportunities, and compare tips on how to approach businesses for career-building positions. Topics such as conducting a residency search, finding an external mentor, and navigating through academic projects are often stressful components of the master of health administration (MHA) curriculum. This stress and confusion can be reduced by engaging students to actively communicate and utilize university resources through the mentor program. Future opportunities exist for growth and expansion of the mentor programs within an existing or newly established MHA program. Key factors to successful integration of the student mentor-mentee program are open communication and transparency between students, program chair, and faculty. This study compares past methods for implementing and running a mentor program, with newer program models. In addition, the various models of mentor programs will be discussed within the academic environment of an MHA program.